Penerapan Blockchain untuk Pengelolaan Dokumen Akademik yang Aman dan Efisien di Politeknik Kutaraja Banda Aceh - Mirnawati; Aini, Zahratul; Khair, Rizaldy (The Indonesian Journal of Computer Science, 2024)
In the modern era of education, academic document management plays a crucial role in supporting the efficiency and sustainability of the academic environment. Given the complexity of information generated by educational institutions, this research focuses on implementing an innovative and integrated document management system. The primary goal of this research is to enhance the security, accessibility, and validity of academic documents, thereby positively impacting the operational effectiveness and quality of educational services. This study is driven by the urgency to improve the security, validity, and efficiency of academic document management at Politeknik Kutaraja Banda Aceh. With technological advancements, document security has become crucial, especially in higher education. Blockchain technology is proposed as an innovative solution to address these challenges. Previous research has demonstrated the relevance of blockchain technology in educational settings, particularly in the management of academic data and documents. The implementation of this technology is expected to provide solutions to issues such as forgery, transparency, and the validity of academic documents, making it essential for improving academic integrity at Politeknik Kutaraja. The aim of this research is to identify and develop a suitable blockchain technology implementation model for managing academic documents within the Polytechnic environment. By utilizing blockchain concepts, the research aims to enhance document security, efficiency in management processes, and the validity of academic documents. The target of this research is the implementation of a distributed system accessible by all relevant stakeholders, a tool for verifying document authenticity, and improving efficiency in managing academic transactions. Through this research, Politeknik Kutaraja is expected to obtain an innovative model to enhance the integrity and security of academic documents, creating a transparent and trustworthy academic environment.